Effect of feedback control with linear and non linear temperature gradients to some convection problems / Adibah Nazarudin - Adibah , Nazarudin (2019)
In many engineering and industrial applications such as crystallization growth process industries, nuclear reactors, solar heating devices and welding of steels, the onset of instability of convection plays a major role in resulting the satisfactory end-products. The linear stability analysis regarding the non-Newtonian convective flow in electro convection and ferrofluids convection in the presence of feedback control strategy is studied by using single-term Galerkin technique. In the case of Bénard–Marangoni electro convection, the presence of feedback control is analysed using the classical linear stability analysis. Linear, parabolic and inverted parabolic temperature profiles are chosen to investigate in this study. For the case of Rayleigh–Bénard–Marangoni ferrofluids convection, the presence of feedback control is analysed and the influence of various parameters on onset is discussed. In the both non-Newtonian fluid, various value of feedback control and other parameters on onset are tested to examine the presence of feedback control on the onset of convection. The results obtained under the limiting conditions compare well with the previous studied. The numerical results obtained are presented graphically and the influences of various parameters are discussed in detail. The results indicate that the value of critical Marangoni number and other parameters affected in the presence of feedback control which delaying the onset of instabilities.